Schools' self-evaluation procedures relevant for primary and secondary schools: variables geometries - Ana Mouraz; Jana Beresova; Carla Figueiredo; Marta Sampaio; Hana Vancova; Daniela Pinto (Instituto Politécnico de Bragança, 2024)
The significance of schools' self-evaluation is intrinsically linked to their autonomy and responsibility in interpreting and executing educational tasks. However, this authority is influenced by both European and national policies. This paper aims to compare the policies and practices underlying the process of school self-evaluation in Slovakia and Portugal. Employing a qualitative approach rooted in comparative research, this study involves analyzing legal documents and field notes collected through informal conversations with school board directors in both countries. While both nations demonstrate some influence from European recommendations in their objectives and procedures, disparities exist in their approaches and emphases. Notably, variations are evident in the purposes of schools' self-evaluation and the teams responsible for conducting it. Nevertheless, both countries underscore the importance of students' achievements within the framework of school self-evaluation.